Development of Arabic Language Teaching Materials Based on The Merdeka Curriculum - Mahdi, Tubagus Ahmad; Mustafa, Izzuddin; Kodir, Abdul; Syafei, Isop (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2025)
Arabic language education in Indonesia must adapt to technological advancement and students' contextual needs. This study aimed to develop Arabic teaching materials based on the Merdeka (Independent) Curriculum and analyze their effectiveness in improving students’ Arabic language skills at MAN Pandeglang, Banten. Employing a Research and Development (R&D) design, the study followed four phases: needs analysis, material development, classroom implementation, and evaluation. The materials were designed using a communicative approach, project-based learning, and digital integration to create an interactive and student-centered learning experience. Needs analysis revealed significant gaps in existing materials, particularly in engaging students and promoting communication. Implementation in classroom settings showed that students responded positively, with greater motivation and participation. Evaluation through pretests and posttests demonstrated significant improvement, especially in speaking and listening skills. The study concludes that the developed materials are effective and suitable for Arabic instruction aligned with the Merdeka Curriculum, contributing to a more relevant, practical, and engaging Arabic learning environment for Indonesian students.